Prevention of Migraine - Holdridge, Ashley; Buczyner, Jennifer; Aymat, Cristina Cabret; Le, Ariel (Seminars in Neurology, 2022)
Migraine, a primary headache disorder is a chronic and complex neurological disease that affects millions of people worldwide, impacting their quality of life. It is one of the most common reasons why individuals seek the advice of their physician, and is one of the most common referrals seen in the offices of general neurologists and headache specialists. In the past decade, there has been robust research on not only the pathophysiology of migraine but in the efforts to treat and, importantly, prevent. The introduction of calcitonin gene related peptide antagonists (CGRP-A) have opened new doors for preventive treatment options. OnabotulinumtoxinA (BoNTA) has remained a staple in the treatment of chronic migraine with data emerging with combination therapy. Neurostimulation has offered additional nonpharmacologic approaches to migraine treatment. In addition to lifestyle and behavioral modifications, these have changed the landscape of migraine prevention.
Keywords: migraine; headache; prevention; treatment; prophylaxis; CGRP